Results of the coriander (Сoriandrum sativum L.) study at different sowing date in the conditions of Absheron - H. G. Hasanov; S. А. Mamedova; H. A. Huseynov (Овощи России)
Relevance.The article presents the results of studying the economic and biological indicators of various coriander samples planted at the Absheron Experimental Base of the Genetic Resources Institute in the autumn and spring, to select the most promising of them and determine the optimal sowing dates that ensure production for most of the year. Material and methods. The research material was the seeds of 5 coriander samples (Coriandrum sativum L.) from various early maturity groups introduced on Absheron: Ordubad (cat. No. 31); Iranian (Cat. No. 87); Azerbaijani (cat. No. 157); Dagestan (cat. No. 171); Borchali (cat. No. 167). When carrying out phenological observations, the onset of economic suitability, bolting, flowering and seed maturation was noted. The total yield from the plot was determined.Results. Phenological observations have shown that depending on the date of coriander samples sowing, the duration of the vegetation period and individual phases of development changed. Sowing dates also significantly affected the early maturity and productivity of the samples, but for different samples to varying degrees. Optimal for the Absheron part of Azerbaijan is the timing of sowing coriander from mid-March to the end of April and in September. The most promising were the coriander samples: Azerbaijan (cat. No. 157), Dagestan (cat. No. 171) and Iranian (cat. No. 87). Sowing at the optimum time of the most productive varieties with a long period of harvest can ensure the uninterrupted supply of fresh coriander greens for most of the year.